Pedological characterization of soils under tobacco cultivation: insights from Sikonge, Uyui and Tabora districts in Tabora Region, Tanzania - Dotto Simon Mwalembe; Boniface H. J. Massawe; Eliakira Kisetu Nassary (Frontiers in Agronomy)
This study investigated pedological characteristics of the soils in Sikonge, Uyui, and Tabora districts in Tabora Region of Tanzania, focusing on their suitability for tobacco (Nicotiana tabacum L.) cultivation. Soil profiles excavated in each district, yielding pedons named TUTUO P1, KIPERA P1, and ISIKIZYA P1, respectively. Standard laboratory methods used to analyze soil texture, bulk density, pH, macronutrients and micronutrients of the soil samples. Results indicated predominantly sandy texture in the studied soils, with Uyui exhibiting loamy sand texture, Sikonge featuring loamy sand and sandy loam, and Tabora comprising sandy clay loam at the surface transitioning to sandy loam and clay in the subsoil. Soil reaction ranged from extremely acid to strongly acid, with pH < 4.5 and pH 5.1-5.5 observed. Nitrogen was notably low across pedons (N< 0.05%). Bulk density exhibited varying trends with depth across districts, ranging from 0.02 to 1.78 g cm-3. Cation exchange capacity increased with soil depth in ISIKIZYA P1 but decreased in TUTUO P1 and KIPERA P1. Available P, varied from very low (0.01 mg kg-1 soil) to medium (15.93 mg kg-1 soil) with increasing depth. Micronutrient analysis revealed elevated copper and iron levels through pedons, zinc deficiency observed in ISIKIZYA P1. Soil classification identified Alfisols, Oxisols and Mollisols, in the respective study areas. The findings revealed notable soil variations, indicating both challenges and prospects for optimizing tobacco production. Tailored soil management is crucial to improve production efficiency.